ANALISIS PERAWATAN ROBOT SPOT UNTUK MENGETAHUI KEANDALAN MESIN PRODUKSI DAN KETERSEDIAAN SPARE PART PADA DEPARTEMENT MAINTENANCE PT. ASTRA DAIHATSU MOTOR JAKARTA - -, Suhartono (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Robot Spot is one of an important machine in production activities of vehicle as-sembly, for example PT. Astra Daihatsu Motor, Jakarta. During production activity, relying on machine is the most significant thing that should be preserved, such as Robot Spot under Body four and Robot Spot Main Body seven. That is suggested; in order con-tinually maintenance could be performed effectively. Relying on of production machines and the willingness spare parts must be accounted to calculate their values of reliability factors, maintainability factors, availability factors and the spare part stocks. Those are approached by goodness of fit test analyses, to predict time and the damaged dis-tributions, life times and the costs of maintenance within the machines. Based on those analyses, both robot spot under body four and robot spot main body seven are having medium reliability with good condition, low rate of damage, and still accurate to be opera-ted. However, it is still necessary to overhaul those machines, so that new machines are not required.